Mapping Research on Differentiated Instruction: A Bibliometric Review of the Literature in the Last 20 Years - Masturdin Masturdin (Journal of Technology-Assisted Learning, 2025)
Differentiated Instruction (DI) has emerged as a vital pedagogical approach over the past two decades, focusing on adapting teaching methods to meet student’s individual needs in heterogeneous classrooms. Introduced by Carol Ann Tomlinson, differentiated instruction enhances learning outcomes, motivation, and active student participation, particularly in classrooms with diverse abilities and needs. Research on differentiated instruction has shown significant growth, both in the number of publications and in the topics explored, such as its application in various subjects, the use of technology, and its impact on different student groups. The United States and Europe are the primary contributors to this research, with leading journals serving as key publication platforms. Future research could benefit from increased collaboration between institutions in these regions and those in the United States and Europe, which could promote the exchange of culturally relevant practices and broaden the application of DI. However, implementing differentiated instruction continues to face challenges, including limited resources, time constraints, and inadequate teacher training. Bibliometric analyses map the development of differentiated instruction research over the past two decades, identifying trends, collaboration networks, and key themes in the literature. This review aims to guide future research and insights for educators, researchers, and policymakers regarding the evolution and implementation of differentiated instruction in education.